CHIRAL ORGANIC POLLUTANTS monitoring and characterization in food and. - Sanganyado, Edmond; Munjanja, Basil K.; Nollet, Leo M. L., 1948- ([S.l.] : CRC PRESS, 2021)
Chiral Organic Pollutants introduces readers to the growing challenges of chirality in synthetic chemicals. In this volume, contributors brilliantly summarize the characteristics of chiral pollutants to provide tools and techniques for effectively assessing their environmental and human health risks. Chapters cover recent research on the physicochemical properties, sources, exposure pathways, environmental fate, toxicity, and enantioselective analysis of chiral organic pollutants. Chiral Organic Pollutants also provides comprehensive discussions on the current trends in the synthesis and legislation of chiral chemicals. Key Features: Includes sampling and analytical methods for the enantioselective analysis of a wide array of chiral organic pollutants in food and the environment Summarizes recent research on the sources, fate, transport, and toxicity of chiral organic pollutants in the environment Critically examines the sources and pathways of chiral organic pollutants such as pesticides, pharmaceuticals, and flame retardants in food Includes a comprehensive discussion on current trends in the enantioselective synthesis and chiral switching of pesticides and pharmaceuticals Provides analysis of current national and international regulations of chiral synthetic chemicals The use of chiral synthetic chemicals such as pesticides, pharmaceuticals, personal care products, and halogenated flame retardants has significantly grown in the past 60 years. Hence, understanding the human and environmental health effects of chiral organic pollutants is crucial in the industry, academia, and policymaking. Chiral Organic Pollutants is an excellent textbook and reference for students, scientists, engineers, and policymakers interested in food quality, environmental pollution, chemical analysis, organic synthesis, and toxicology. Also available in the Food Analysis and Properties Series: Analysis of Nanoplastics and Microplastics in Food, edited by Leo. M.L. Nollet and Khwaja Salahuddin Siddiqi (ISBN: 9781138600188) Proteomics for Food Authentication, edited by Leo M.L. Nollet, and Semih tle (ISBN: 9780367205058) Mass Spectrometry Imaging in Food Analysis, edited by Leo M.L. Nollet (ISBN: 9781138370692) For a complete list of books in this series, please visit our website at: www.crcpress.com/Food-Analysis--Properties/book-series/CRCFOODANPRO
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Chemistry / General; Organic wastes -- Environmental aspects; Organic wastes -- Toxicology; Chirality; Food -- Analysis